2018
DOI: 10.1002/lary.27503
|View full text |Cite
|
Sign up to set email alerts
|

Mandated wrapping of airway cart instruments: Limited access without the intended safety benefits

Abstract: Objectives/Hypothesis Isolated case studies have shown improper sterilization or contamination of equipment from anesthesia carts can lead to transmission of disease and even death. Citing this literature, national accrediting agencies mandated all instruments in the otolaryngology airway carts at San Antonio Military Medical Center be packaged to prevent contamination. This study sought to determine the infection and safety implications of packaged airway cart instruments. Study Design Retrospective chart rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…A recent retrospective chart review compared infection rates and time to assemble instruments for two groups of 100 patients, one before and the other after such a policy was implemented for otolaryngology airway carts at a single institution. This revealed that neither the infection rate nor length of hospital stay decreased and that the time required for equipment assembly doubled [ 17 ]. Another study reported that reducing the amount of packaging on the emergency airway cart reduced both assembly time and time to visualization of the trachea by two to four minutes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent retrospective chart review compared infection rates and time to assemble instruments for two groups of 100 patients, one before and the other after such a policy was implemented for otolaryngology airway carts at a single institution. This revealed that neither the infection rate nor length of hospital stay decreased and that the time required for equipment assembly doubled [ 17 ]. Another study reported that reducing the amount of packaging on the emergency airway cart reduced both assembly time and time to visualization of the trachea by two to four minutes [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…While maintaining airway equipment in unopened sterile packaging may reduce the risk of nosocomial pneumonia, there is no evidence of increased pneumonia risk from using sterilized, opened equipment stored in a clean, but not sterile, manner 1,2 . Bacteria detected in nosocomial pneumonia after endotracheal intubation are normally oral flora, 3 and these bacteria are not found growing on preprepared endotracheal tubes.…”
Section: Commentmentioning
confidence: 99%
“…While maintaining airway equipment in unopened sterile packaging may reduce the risk of nosocomial pneumonia, there is no evidence of increased pneumonia risk from using sterilized, opened equipment stored in a clean, but not sterile, manner. 1,2 Bacteria detected in nosocomial pneumonia after endotracheal intubation are normally oral flora, 3 and these bacteria are not found growing on preprepared endotracheal tubes. As a compromise with the Infection Control and Prevention Department, the authors were permitted to store airway equipment in an opened state inside a wipeable plastic box on the front shelf of each anesthesia machine in L&D, ensuring readiness for emergency use.…”
Section: Commentmentioning
confidence: 99%
“…The maneuverability and light function of unopened packaged laryngoscope blades and handles cannot be tested before assembly, posing a potential risk if the equipment malfunctions.While maintaining airway equipment in unopened sterile packaging may reduce the risk of nosocomial pneumonia, there is no evidence of increased pneumonia risk from using sterilized, opened equipment stored in a clean, but not sterile, manner. 1,2 Bacteria detected in nosocomial pneumonia after endotracheal intubation are normally oral flora, 3 and these bacteria are not found growing on preprepared endotracheal tubes. As a compromise with the Infection Control and Prevention Department, the authors were permitted to store airway equipment in an opened state inside a wipeable plastic box on the front shelf of each anesthesia machine in L&D, ensuring readiness for emergency use.The authors advocate for a more rational approach by The Joint Commission (TJC) and Centers for Disease Control and Prevention (CDC) regarding sterile packaged airway equipment.…”
mentioning
confidence: 99%
“…While maintaining airway equipment in unopened sterile packaging may reduce the risk of nosocomial pneumonia, there is no evidence of increased pneumonia risk from using sterilized, opened equipment stored in a clean, but not sterile, manner. 1,2 Bacteria detected in nosocomial pneumonia after endotracheal intubation are normally oral flora, 3 and these bacteria are not found growing on preprepared endotracheal tubes. As a compromise with the Infection Control and Prevention Department, the authors were permitted to store airway equipment in an opened state inside a wipeable plastic box on the front shelf of each anesthesia machine in L&D, ensuring readiness for emergency use.…”
mentioning
confidence: 99%